ECONOMIC VALUATION OF "BEEJAY BAKAU RESORT (BJBR)" MANGROVE FOREST TOURISM PROBOLINGGO AND IT IS IMPACT TO THE ENVIRONMENT TOWARDS SUSTAINABLE RESOURCE MANAGEMENT - Muhammad Fajar Maulana; S Suhartini; F Fahriyah (Agricultural Socio-Economics Journal, 2022)
Economic growth often occurs at the expense of the quality of natural resources and the environment because of the impact caused by economic activity. These impacts create external costs that the public and future generations must bear. Internalization of external costs must be enforced to prevent damage to natural resources and the environment (ex-ante strategy) or repair the damage that has occurred (ex-post strategy). Therefore, economic valuation is needed to provide important information regarding the value of ecosystems and the resulting economic benefits, especially for non-market environmental goods that have important policy implications and as an effort to achieve the Sustainable Development Goals (SDGs). This study aimed to analyze and estimate the economic value and identify the ecological, social and economic impacts at BeeJay Bakau Resort Probolinggo. Types of descriptive research with data collection methods include interviews, observations, documentation, and questionnaires. The sampling method used 2 methods: the accidental sampling technique for tourists by determining the number of samples using the linear time function formula so that a total sample of 84 respondents was obtained and the purposive sampling technique for stakeholders with a sample of 40 respondents. The results of the analysis show that the economic value generated is Rp. 584,347,909,947/year. The output of identification of ecological, economic and social impacts which includes three dimensions, namely the ecological, economic and social dimensions, each of which has 4 defined attributes, then it can be concluded that the ecological dimension has a high category, this is because the manager of the BeeJay Bakau Resort mangrove forest tourism carry out various efforts in development that involve both stakeholders and the surrounding community, especially in maintaining and committing to environmental sustainability.